Research on co-simulation of multi-resolution models based on HLA. (May 2023) - Cao, Qi
Intelligence, hierarchy, and multi-resolution (MR) modeling are vital to the complex system simulation. Based on the proposed MR-Agent-Discrete EVent System (MR-Agent-DEVS) specification, this paper discusses the co-simulation of MR models under high-level architecture (HLA). First, the structure and formal description of MR-Agent-DEVS federate models were proposed. The communication mechanism and simulation process of MR-Agent-DEVS federate models were analyzed. Finally, an example of distributed interactive simulation for emergency material supply was given. The results of the simulation test show that HLA enhances the reusability of MR-Agent-DEVS models, knowledge updating and model coupling enrich the interoperability of MR-Agent-DEVS models, and the real-time memory of knowledge base in Agent ensures the consistency of MR-Agent-DEVS models in aggregation and disaggregation.